1991
DOI: 10.1007/bf02265156
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of hepatic triacylglycerol lipase isolated from rainbow trout,Oncorhynchus mykiss

Abstract: Trialcylglycerol (TG) lipase was isolated and partially purified from rainbow trout liver. Triacylglycerol lipase activity was assayed by measuring(14)C-oleic acid release from(14)C-triolein.(14)C-oleic acid release was linear for up to two hours. Optimal activity occurred at pH 7.0 and 15°C. Most of the lipase activity was recovered in the cytosolic fraction. A 27,000-fold purification was achieved after Sepharose (Bio-gel A 0.5 M, 200-400 mesh) chromatography of a resuspended 20% ammonium sulfate fraction. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Protein bands were purified and reduced to a single homogenate band with 70 kDa molecular weight in ion exchange chromatography, DEAE-Cellulose. Other studies found the molecular weight as 74 kDa for liver lipase of C. carpio [14], 87 kDa for lipase from the dorsal part of Cirrhinus reba [15], 40-43 kDa for O. mykiss liver lipase [20], 43 kDa for S. aurita digestive lipase [27]. As can be seen from these results, we may conclude that lipases have different molecular weight depending on the tissue and the fish species under investigation.…”
Section: Sds-pagesupporting
confidence: 53%
See 2 more Smart Citations
“…Protein bands were purified and reduced to a single homogenate band with 70 kDa molecular weight in ion exchange chromatography, DEAE-Cellulose. Other studies found the molecular weight as 74 kDa for liver lipase of C. carpio [14], 87 kDa for lipase from the dorsal part of Cirrhinus reba [15], 40-43 kDa for O. mykiss liver lipase [20], 43 kDa for S. aurita digestive lipase [27]. As can be seen from these results, we may conclude that lipases have different molecular weight depending on the tissue and the fish species under investigation.…”
Section: Sds-pagesupporting
confidence: 53%
“…Optimum temperature was found to be 15°C for O. mykiss liver lipase [18], 37°C in Cyprinuscarpio [14], 25°C to 30° C for Gadusmorhua digestive lipase [16] and 35°C for C. reba dorsal part lipase [15].…”
Section: Physical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, further addition of INS would inhibit the actions of GLU, stopping the lipolytic actions of lipase enzymes. Trout liver is known to possess a lipase which is activated by phosphorylation (Harmon et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were resuspended in Hank's buffer and homogenized. Following centrifugation (16 000 g for 10 min at 14 8C), the supernatant was removed, separated, and subjected to 20% ammonium sulfate fractionation; the HSL-containing precipitate (Harmon et al 1991) was collected after ice incubation (30 min) and centrifugation (16 000 g for 15 min). HSL samples were resuspended in a buffer (25 mM Tris-HCl, pH 7.4) and subjected to SDS-PAGE.…”
Section: Hormone-modulated Phosphorylationmentioning
confidence: 99%